Frequency of Monoclonal Gammopathy in Hyperproteinaemic Patient - Rahman, Md Safiur; Uddin, Mohammad Mosleh; Rahman, Md Moshiur (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Paraproteinemia or monoclonal gammopathy is the presence of excessive amounts of a single monoclonal gammaglobulin (In this case denominated "paraprotein") in the blood. It is usually due to an underlying immunoproliferative disorder and sometimes considered equivalent to plasma cell dyscrasia. To determine the frequency of monoclonal gammopathy in hyperproteinemic patient, to interpretate serum protein electrophoresis, distribution of monoclonal gammopathy in relation to age and sex. Materials and methods: An observational, descriptive, cross sectional study was taken place at Armed Forces Institute of Pathology (AFIP) Dhaka Cantonment, Dhaka from May 2017 - October 2017. A total of 165 hyperprotei- nemic patients at all age and sex were included to the study and hypoproteinaemic, normoproteinaemic patients and pregnancy were excluded. Six millilitres venous blood was collected asceptically from each patient. Results: About 12.1% of monoclonal gammopathy was found in hyperproteinemic patients. Among them 66.1% were men and 33.9% were female. Common age group was 41-60 and 61-80. Conclusion: The treatment, monitoring and prognosis of monoclonal gammopathy depends on the early detection of M protein band in electrophoretic pattern. This study reveals a high incidence of monoclonal gammopathy in patients with hyperproteinemia and frequency is increasing with higher age. So serum protein electrophoresis should be done for all hyperproteinemic patients. JCMCTA 2020 ; 31 (2) : 25-30